Industrial and commercial sector comparability of financial statements of listed companies in Singapore. - Ong, Fung Yin. (2008)
This study aims to determine the inter-company and inter-period comparability of the financial statements of listed companies in the Industrial and Commercial sector in Singapore. This study extends only to Singapore incorporated companies from 1987 to 1996. This study concentrates on nine accounting policies - inventory valuation, depreciation, construction contracts, dividend income, income tax, long-term investments, short-term investments, associated companies and foreign currency translation.